Water-soluble MoS2 quantum dots for facile and sensitive fluorescence sensing of alkaline phosphatase activity in serum and live cells based on the inner filter effect. Issue 45 (13th November 2018) - Zhong, Yaping; Xue, Fengfeng; Wei, Peng; Li, Ruohan; Cao, Chunyan; Yi, Tao
Abstract : We report a facile and sensitive method for the detection of alkaline phosphatase (ALP) activity in serum and live cells using molybdenum disulfide quantum dots (MoS2 QDs) based on the Inner Filter Effect (IFE). Abstract : We report a facile and sensitive method for the detection of alkaline phosphatase (ALP) activity in serum and live cells using molybdenum disulfide quantum dots (MoS2 QDs) based on the Inner Filter Effect (IFE). In the present work, water soluble MoS2 QDs with bright green fluorescence were synthesized through direct ultrasonic exfoliation of MoS2 powder in 85 vol% aqueous ethanol solution. p -Nitrophenylphosphate (PNPP) was employed to act as an ALP substrate, and its enzyme catalytic product ( p -nitrophenol (PNP)) functioned as a powerful absorber in the IFE to influence the excitation of MoS2 QDs. PNPP was transformed into PNP in the presence of ALP, leading to the transition of the absorption peak from 310 nm to 405 nm and therefore resulted in a complementary overlap between the absorption of PNP and the excitation of MoS2 QDs. The fluorescence of MoS2 QDs was quenched due to the significant weakening of the excitation of MoS2 QDs by competitive absorption between QDs and PNP. A good linear relationship was obtained from 0 to 5 U L −1 ( R 2 = 0.9919) using the present IFE based sensing strategy with the lowest detection activity of 0.1 U L −1 . The proposed sensing approach was successfully applied to ALP sensing in serum samples and ALP inhibitor investigation, as well as in ALP cell imaging.